Implementasi Sabar dalam Mendidik Anak Tunagrahita - Syifani, Cindhea (Jurnal Riset Agama, 2023)
This study aims to identify the implementation of patience of teachers at SLB-C Silih Asih in educating mentally retarded children. This research is a type of field research using a qualitative approach, which places the researcher as the core instrument, in which the result of the study will be greatly influenced by the ability of the researcher to analyze and interpretation. Interviews and observation were used as data collection techniques so that the data obtained were more comprehensive. This study found that teachers at SLB C Silih Asih are also patient individuals and implement patience in educating mentally retarded children. The methods used by the teacher include the method of communication, simulation, practice and prompts. This method serves to catch up with various delays form mentally retarded children. The use of this method will certainly be more effective if it is realized patiently. Based on the result of interviews, the method has been carried out with great patience in order to achieve the expected goals.Â Based the research findings, it was concluded that the subjects were patient individuals and had applied in the learning process.